2020
DOI: 10.3389/fimmu.2020.00178
|View full text |Cite
|
Sign up to set email alerts
|

FTY720 Exerts Anti-Glioma Effects by Regulating the Glioma Microenvironment Through Increased CXCR4 Internalization by Glioma-Associated Microglia

Abstract: Background: Glioblastoma (GBM) is one of the most malignant and aggressive primary brain tumors. The incurability of glioblastoma is heavily influenced by the glioma microenvironment. FTY720, a potent immunosuppressant, has been reported to exert anti-tumor effects in glioblastoma. However, the impact of FTY720 on the glioma microenvironment remains unclear. Methods:We examined the effects of FTY720 on the distribution and polarization of glioma-associated microglia and macrophages (GAMs) in glioma-bearing rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…FTY720 is FDA approved for the treatment of multiple sclerosis, and it is currently under trial for the treatment of breast carcinoma, glioblastoma and anaplastic astrocytoma (NCT03941743 and NCT02490930). FTY720 has several anticancer effects [ 77 , 78 , 79 , 80 , 81 ] but its activity in OS has not been explored so far. Despite being considered an S1P receptor modulator, FTY720 is also able to induce changes in the enzymes of the sphingolipid pathway, including SPHK1 [ 54 , 55 , 56 ], thus providing an explanation for the reduction of S1P seen in our model.…”
Section: Discussionmentioning
confidence: 99%
“…FTY720 is FDA approved for the treatment of multiple sclerosis, and it is currently under trial for the treatment of breast carcinoma, glioblastoma and anaplastic astrocytoma (NCT03941743 and NCT02490930). FTY720 has several anticancer effects [ 77 , 78 , 79 , 80 , 81 ] but its activity in OS has not been explored so far. Despite being considered an S1P receptor modulator, FTY720 is also able to induce changes in the enzymes of the sphingolipid pathway, including SPHK1 [ 54 , 55 , 56 ], thus providing an explanation for the reduction of S1P seen in our model.…”
Section: Discussionmentioning
confidence: 99%
“…FTY720 could inhibit the growth, migration, and invasion of glioma by targeting GAMs to impede their effect on glioma cells, while also potentially blocking the chemoattraction of GAMs by inhibiting the MAPK-mediated secretion of IL-6 through the increased internalization of CXCR4. Microglia and macrophages are polarized from pro-glioma to an anti-tumor phenotype [ 89 ]. Zhang et al showed that GAMs display a continuum of different polarization states between anti-tumorigenic and pro-tumorigenic macrophage phenotypes.…”
Section: Therapeutic Benefitsmentioning
confidence: 99%
“…In long-term usage, this was shown to increase the risk of cancer development [ 158 ]. Subsequent investigations revealed that fingolimod decreased recruitment of macrophages to the brain tumor microenvironment, as well as pushed them toward a proinflammatory (M1) phenotype via C-X-C Motif Chemokine Receptor 4 (CXCR4) internalization [ 159 ]. Outside of the tumor setting, mice without S1P lyase expression had greater microglial activation in the brain.…”
Section: Immune Traffickingmentioning
confidence: 99%